1999
DOI: 10.1038/sj.bjp.0702835
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chemokine CCR3 agonist‐mediated eosinophil recruitment in the Brown‐Norway rat

Abstract: 1 The ability of various C-C chemokines to elicit tissue eosinophil in®ltration following intradermal injection or peripheral blood eosinophilia following intravenous injection were compared in the Brown-Norway rat. 2 Eotaxin (0.1 ± 3 mg site 71 ) of human and murine origin produced equivalent, dose-dependent increases in eosinophil peroxidase activity in rat dermis 4 h post-injection. 3 Human eotaxin-2 was equipotent with human eotaxin in terms of dermal eosinophil recruitment. Other human CCR3 agonists, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…CCL11 injection (29). Later on, it has been demonstrated that human CCL11 is able to cause a dose-dependent increase of circulating eosinophils in the BN rat, which is ϳ3-fold higher than the vehicle (33). The increased mobilization in F344 rats expressing DPPIV is similar, peaking 30 min after i.v.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…CCL11 injection (29). Later on, it has been demonstrated that human CCL11 is able to cause a dose-dependent increase of circulating eosinophils in the BN rat, which is ϳ3-fold higher than the vehicle (33). The increased mobilization in F344 rats expressing DPPIV is similar, peaking 30 min after i.v.…”
Section: Discussionmentioning
confidence: 53%
“…The cutaneous recruitment of eosinophils in rats is supposed to be modulated by DPPIV, as it has been shown that DPPIV is present in rat epidermis (35). Furthermore, the capacity of human CCL11 to attract eosinophils to rat skin has been shown previously (33). A dose-dependent infiltration could be observed in DPPIV pos and DPPIV neg rats.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Rodent, human, and murine eotaxin1 have been shown to be equieffective in terms of inducing eosinophil chemotaxis in vivo (Kudlacz et al, 1999). In this study, human eotaxin1 caused a marked increase in leukocyte recruitment after 6 h when administered to the air pouch of ovalbumin-sensitized mice pretreated with IL-5.…”
Section: Discussionmentioning
confidence: 77%
“…Human CCR3 binds Eotaxin-1, Eotaxin-2, Eotaxin-3 and MCP-4 with high affinity, whereas RANTES and MCP-3 bind with lower affinity. Guinea pig Eotaxin-1 is highly potent as a stimulator of human eosinophils ) but, conversely, human Eotaxin-1 is inactive on guinea pig cells, although it is active on rat eosinophils (Sanz et al 1998, Kudlacz et al 1999. Despite the fact that human RANTES stimulates human eosinophils, RANTES from other species has, in general, low activity on homologous eosinophils (Campbell et al 1997).…”
Section: The Eotaxin Receptor Ccr3mentioning
confidence: 99%